2011
DOI: 10.1002/jmri.22549
|View full text |Cite
|
Sign up to set email alerts
|

MRI for staging lymphoma: Whole‐body or less?

Abstract: Purpose: To assess whether whole-body MRI detects more clinically relevant lesions (i.e., leading to a change in Ann Arbor stage) than an MRI protocol that only includes the head/neck and trunk (i.e., from cranial vertex to groin, excluding the arms) in patients with lymphoma. Materials and Methods:One hundred consecutive patients with newly diagnosed lymphoma prospectively underwent T1-weighted and T2-weighted short inversion time inversion recovery whole-body MRI. The number of lymphomatous sites at MRI with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Scan time is important from a capacity point of view, and specifically to attenuate motion artifact in non-sedated children. It has been suggested that restricting MRI to head, neck, and trunk is non-inferior to whole-body MRI for staging of lymphoma (9).…”
Section: Staging Of Lymphomamentioning
confidence: 99%
“…Scan time is important from a capacity point of view, and specifically to attenuate motion artifact in non-sedated children. It has been suggested that restricting MRI to head, neck, and trunk is non-inferior to whole-body MRI for staging of lymphoma (9).…”
Section: Staging Of Lymphomamentioning
confidence: 99%